2021
DOI: 10.1108/bfj-02-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

A repurchase intention model of Indonesian herbal tea consumers: integrating perceived enjoyment and health belief

Abstract: PurposeThis research seeks to develop a model to predict repurchase intention based on the modified theory of planned behavior (TPB).Design/methodology/approachThis research is quantitative study involving 150 respondents from five major cities in Indonesia. Data were collected using a questionnaire. Data analysis used confirmatory factor analysis–structural equation modeling (CFA–SEM).FindingsThe research instrument and the proposed model were fit. However, health belief was not proven to have a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 100 publications
(136 reference statements)
3
5
0
Order By: Relevance
“…In research (Yusuf et al, 2018) it is stated that generation Y is the generation that buys the most rice, including organic rice. Sources : (Astrini et al, 2021;Hwang et al, 2021;Ngubelanga & Duffett, 2021;and Vladova et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In research (Yusuf et al, 2018) it is stated that generation Y is the generation that buys the most rice, including organic rice. Sources : (Astrini et al, 2021;Hwang et al, 2021;Ngubelanga & Duffett, 2021;and Vladova et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Research using the perceived enjoyment variable is rarely carried out by many other researchers, especially mediated by the attitude variable which can influence the repurchasing intention variable (Astrini et al, 2021). According to (Astrini et al, 2021) perceived enjoyment is a variable that represents trust in an emotional reaction that comes from a person's attitude. This research will measure whether consumers consuming organic rice will create a happy attitude and a sense of relaxation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior HCI and technology acceptance literature has primarily argued that perceived enjoyment has importance to determine the intention to use new systems and applications ( Davis et al, 1992 ; Venkatesh, 2000 ; Van der Heijden, 2004 ; Venkatesh et al,2012 ), such as SM. Perceived enjoyment has an effect on health belief ( Astrini et al, 2021 ). Based on the above theoretical support, it can be concluded that perceived enjoyment fits into Attribute 2 of BST in the HCI lens.…”
Section: Theoretical Frameworkmentioning
confidence: 99%